A study on CLIL secondary school teachers in Spain: Views, concerns and needs - Senra-Silva, Inmaculada (Complutense Journal of English Studies, 2021)
Content and Language Integrated Learning (CLIL) is a methodological approach that is growing very fast in many European countries, particularly in Spain. The implementation of bilingual programmes in primary, secondary and tertiary education has produced significant changes that have had direct consequences on all educational stakeholders, including teachers, parents and students. In the case of CLIL teachers, research has often addressed their training needs, and actions towards preparing them for successful classes have been proposed. However, few studies have focused on their concerns and views of bilingual programs. Despite the fact that many researchers have acknowledged the importance of understanding CLIL teachers’ views and beliefs, thus hoping for more studies on those issues, this is not yet one of the major research targets. In this study CLIL secondary school teachers in Spain were approached in order to identify the problems they encounter when implementing CLIL. An online questionnaire with both open and close questions was designed administered to informants across Spain. The findings reveal that, overall, the difficulties teachers encounter when implementing a bilingual programme are multiple, and many informants believe that the bilingual programme in English needs a comprehensive reform in Spain.